The outcome of instrument-assisted soft-tissue mobilization in conjunction with functional training in a patient with chronic regional pain syndrome post-supraspinatus arthroscopic repair (Indian Journal of Case Reports, 2020)
Chronic regional pain syndrome (CRPS) is a condition that shows extreme pain that is disproportionate in time and intensity. Instrument-assisted soft-tissue mobilization is a new range of tools that enable clinicians to efficiently locate and treat individuals diagnosed with soft-tissue dysfunction. Here, we report the case of a 50-year-old female who was diagnosed with high-grade partial articular surface supraspinatus tear which was surgically managed by arthroscopic repair. A thorough assessment revealed that there was a severe restriction of shoulder ranges and pain. She was into Stage I of CRPS. Usually, in CRPS, the mainstay of treatment is pain block or dry needling or painkillers such as nonsteroidal anti-inflammatory drugs and tramadol before starting the exercises. However, she was initially treated with instrument-assisted soft-tissue release and subsequently given functional training for the improvement in range of movements and control. There was not only a considerable improvement in her range but also a reduction in the pain within 12-week post-operative. Thus, we can conclude that instrument-assisted soft-tissue release and functional training not only helped to ameliorate her pain and improved the range but also gave her a sense of active involvement in her household chores.